Pengaruh Kreasi Nilai Merek secara Personal dan Komunal Terhadap Ekuitas Merek Klinik Bunda Labuan Bajo - Paulina Febrianty; Rohendi Rohendi; Oke Andikarya (CV. Ulil Albab Corp, 2026)
Klinik Bunda Labuan Bajo has experienced a steady increase in patient visits; however, this growth has not been accompanied by a strengthening of its brand equity. The decline in its Google rating, despite a rising number of reviews, indicates the presence of unresolved complaints and a relatively narrow gap between positive and negative feedback. This pattern suggests the possibility of underlying issues that are not immediately visible yet may weaken overall brand perception. This study aims to analyze the influence of personal and communal brand value co-creation on the brand equity of Klinik Bunda Labuan Bajo. Data were collected through questionnaires distributed to 101 patients using the Lemeshow sampling formula. The data were analyzed using qualitative analysis and multiple linear regression. The results demonstrate that both personal and communal brand value co-creation have a significant and positive effect on brand equity. The significance indicates that these forms of value co-creation genuinely influence brand equity, while the positive direction reflects that increases in personal and communal value co-creation correspond to increases in brand equity, and decreases in these constructs are associated with declines in brand equity.